Arabidopsis UBC22, an E2 able to catalyze lysine-11 specific ubiquitin linkage formation, has multiple functions in plant growth and immunity. (August 2020) - Wang, Sheng; Li, Qiang; Zhao, Liang; Fu, Sanxiong; Qin, Li; Wei, Yangdou; Fu, Yong-Bi; Wang, Hong
Highlights: The ubc22 knockout mutant plants showed four subtypes based on morphology. Transcriptomic analysis revealed distinct changes of gene expression in different subtypes of the mutant plants. UBC22 has multiple functions and is involved in plant immunity. Abstract: Protein ubiquitination is critical for various biological processes in eukaryotes. A ubiquitin (Ub) chain can be linked through one of the seven lysine (K) residues or the N-terminus methionine of the Ub, and the Ub-conjugating enzymes called E2s play a critical role in determining the linkage specificity of Ub chains. Further, while K48-linked polyubiquitin chain is important for protein degradation, much less is known about the functions of other types of polyubiquitin chains in plants. We showed previously that UBC22 is unique in its ability to catalyze K11-dependent Ub dimer formation in vitro and ubc22 knockout mutants had defects in megasporogenesis. In this study, further analyses of the Arabidopsis ubc22 mutants revealed four subtypes of plants based on the phenotypic changes in vegetative growth. These four subtypes appeared consistently in the plants of three independent ubc22 mutants. Transcriptomic analysis showed that transcript levels of genes related to several pathways were altered differently in different subtypes of mutant plants. In one subtype, the mutant plants had increased expression of genes related to plant defenses and showed enhanced resistance to a necrotrophic plant pathogen. These results suggest multiple functions of UBC22 during plant development and stress response.